Antiulcer activity of ethanolic extract of Arctocarpus hirsutus Lam. leaves in albino Wistar rats - B N, Chaithra; D’Souza, Ullas Prakash; Khandige, Prasanna Shama; Sadananda, Vandana (Journal of Applied Pharmaceutical Research, 2023)
Peptic ulcers, a prevalent gastrointestinal disorder, remain a significant health concern. Artocarpus hirsutus Lam., a plant deeply rooted in traditional medicine, has been historically employed to address various health issues. Each component of this plant showcases diverse therapeutic activities, offering a holistic approach to health concerns. This study aimed to explore the gastroprotective and antiulcerogenic potential of the ethanol-based extract derived from Artocarpus hirsutus Lam leaves. Administered orally in 100, 200, and 400mg/kg doses, the extract's effects were compared with established medications - omeprazole (30mg/kg) and sucralfate (100mg/kg). Parameters such as gastric acid volume, gastric pH, ulcer index, total acidity, and free acidity were evaluated. The ethanol-based extract derived from Artocarpus hirsutus Lam. leaves demonstrated activity at doses of 200mg/kg and 400mg/kg, resulting in a marked decrease in free acidity, total acidity, gastric volume, ulcer index, and an increase in gastric pH compared to the ulcer control group. Notably, the ethanol-based extract of leaves of Artocarpus hirsutus Lam. exhibited significant gastroprotective and ant-ulcerogenic effects in both ethanol induced ulcer and pylorus ligated ulcer models. These findings underscore the potential therapeutic value of Artocarpus hirsutus Lam. as an effective agent against peptic ulcers, supporting its traditional use in holistic health practices.